(untitled) (Proceedings of the Global Public Health Conference, 2022)
We explored mental well-being among university students during the first 12 months of the COVID-19 pandemic, and whether those experiences differed as a function of generation status. Data were collected as part of the researchers’ participation in the COVID-19 University Research on Education and Sustainability (CURES) Project, a multi-site study of adjustment among college students during the pandemic. University students (N = 395, average age = 21 years) completed a measure of COVID-19-related stress, the CESD-10 depression inventory, and the GAD-7 anxiety scale. They also reported whether they had received any mental health treatment and whether they had seriously thought about and/or attempted suicide since the start of the pandemic. Although research has documented multiple (pre-pandemic) mental health differences between first- and continuing-generation students, we found none. A multivariate analysis of variance revealed no significant effects for generation status on the three multi-item measures; first-and continuing-generation students reported equally high levels of COVID-19-related stress, depression, and anxiety. Thirty percent of students reported the onset of suicidal ideation and/or suicide attempts after the start of the COVID-19 pandemic (no generation status differences). Few students (16%) had received mental health treatment since the start of the pandemic (no generation status differences). The pandemic appears to have blurred prior differences between first- and continuing-generation students and to have exacerbated the challenges faced by all students. Identifying these challenges is an essential first step toward developing methods for enhancing student well-being as we move through and beyond the COVID-19 pandemic.